Procedural memory and syntactic complexity in Spanish students - Alfaro-Faccio, Pedro; Figueroa-Leighton, Alejandra (Lenguas Modernas, 2020)
This research (Fondecyt Proyect 11160978) aims to determine the influence of procedural memory levels on syntactic complexity in school-age subjects with typical linguistic and cognitive development. For this reason, a retrospective ex post facto research was conducted in which 119 subjects were evaluated. These subjects were divided into five groups of different school levels: preschool, second grade, fourth grade, sixth grade, and eight grade from primary school. In terms of procedural memory, an implicit learning serial reaction time (SRT) task was applied using visual-spatial series. To report syntax, we conducted an analysis of nodes of syntactic dependency present in oral narratives retold by subjects. Data was correlated and therefore a linear regression model was applied to predict the influence of one variable over the other. Results revealed significant correlations (<1.96 according to the standard index value) in each group (preschool=0.72; second grade=0.75; fourth grade=0.74; sixth grade=0.79; eight grade=0.70). The regression model reported R 2 values over to 0.5.